2003
DOI: 10.1258/002221503321626375
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of heat to the vestibule during revision stapes surgery using a KTP laser: an in vitro study

Abstract: The transmission of heat to the vestibule during revision stapes surgery with a piston in situ has been studied using a KTP laser in an in vitro model. A type K thermocouple was placed around the medial of each piston tested in a 'vestibule' filled with saline. The effect of laser hits on fluoroplastic, fluoroplastic-wire and stainless steel stapes prostheses was investigated. The effect of adding blood to the operative field, of introducing a vein graft to seal the stapedotomy and of vaporizing soft tissue in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Regardless of the laser type used, if there is a piston in situ, there is a risk that it will be hit by the laser during the procedure. Szymanski et al have investigated the possible heating of the vestibule during KTP laser revision surgery, in an in vitro model 30 . They found only modest temperature rises, even when the piston was hit on numerous occasions.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the laser type used, if there is a piston in situ, there is a risk that it will be hit by the laser during the procedure. Szymanski et al have investigated the possible heating of the vestibule during KTP laser revision surgery, in an in vitro model 30 . They found only modest temperature rises, even when the piston was hit on numerous occasions.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies showed that the KTP laser may damage fluoroplastic pistons, especially when blood was added to the surface of the piston. Data from our previous work on the KTP laser 5 did not support these results. We showed that applying the KTP laser to fluoroplastic or stainless steel pistons, using the manufacturer's recommended power settings, was not likely to cause inner-ear irritation or piston damage.…”
Section: Introductionmentioning
confidence: 57%
“…In our previous study, 5 we concluded that there was little risk of inner-ear trauma following use of the KTP laser on stapes pistons. Despite the different properties of the KTP laser (wave length 532 nm) and CO 2 laser (wave length 10 600 nm), the results of both series of experiments are comparable.…”
Section: Discussionmentioning
confidence: 83%
“…Two recent experimental studies by Szymanski et al88, 89 use thermocouples and a saline‐filled vestibule stapes/middle ear model with a stapes prosthesis to measure laser‐related temperature changes. Varying conditions were arranged: prosthesis only, prosthesis with blood applied, and prosthesis with a vein graft under the tip.…”
Section: Introductionmentioning
confidence: 99%